The Psychotherapeutic Conversation of Novice and Expert. an Exploratory Study in Chile [la Conversación Psicoterapéutica de Experto y Novato. Un Estudio Exploratorio en Chile] - Villalta-Paucar, M (Fundacion Aigle, 2019)
Psychotherapy studies sustain the change in communication theories, reflecting the importance of relationship between language and change. The purpose of the present case study is to understand, through the analysis of dialogue, the organization of the psychotherapeutic conversation and the construction of shared meanings articulated in different therapeutic contexts. The results show that the therapeutic conversation is organized in linguistic structures of "Exchange", no matter the diverse therapeutic contexts, with differences only in use and production, according to the level of expertise of the psychologist. Each type of "Exchange" makes explicit joint and interdependent forms of interventions linked to the interlocutors. The study also proposes, although in an incipient way, formative elements of psychologists. © 2019 Fundación AIGLÉ.